Legacy of Heroic Values Education KH. Abdullah Sajjad from Madura Assisted with Learning Comics for SD/MI Students in Sumenep - Muhammad Misbahudholam AR; Surya Fajar Rasyid; M. Ridwan (Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2021)
The purpose of this research is First, describing the educational value of KH Abdullah Sajjad from Madura on elementary school/MI students. Second, describe the strategy of implementing the education value of KH Abdullah Sajjad uses comic learning in elementary school. This research method uses a qualitative approach that orates to the exposure of education implementation of the value of heroes from students or caregivers. The educational values of KH heroism Abdullah was time to disseminate, especially to elementary school-aged children and ibtidaiyah. From the data obtained, KH. Abdullah Sajjad bequeathed the values of leadership, courage, spirit of nationalism and patriots, togetherness and responsibility, love of the homeland, willing to sacrifice selflessly.